Long cycling stability imparted to li-ion batteries by conjugated polymers with low dihedral angles and high electron density on functional groups - Kargude, Radhakisan; Srinivasalu, Hari Haran; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam (ACS Applied Polymer Materials, 2025)
In conjugated polymers, dihedral angles at bonds connecting their monomers impact the polymers' properties such as the packing of the polymer chains, bandgap, and conductivity. These properties are expected to impact the performance of rechargeable Li-ion batteries because the Li-ion transport and conductivity of the polymers are two important parameters. To understand this, we designed and synthesized two polymers with two different dihedral angles. The polymer, Poly(EDOT-DPP), comprising diketopyrrolopyrrole (DPP) and ethylenedioxythiophene (EDOT) as monomers, showed a low dihedral angle of 2 degrees. On the other hand, the polymer, Poly(EDOT-i-Ind), comprising EDOT and i-Indigo (i-Ind) showed a dihedral angle of 17 degrees. Density functional theory (DFT) studies showed that the electron density at the carbonyl moiety of EDOT-DPP is higher than that of EDOT-i-Ind. This resulted in a higher Li+ binding energy of -3.665 eV for EDOT-DPP and a lower Li+ binding energy of -3.464 eV for EDOT-i-Ind. Battery electrodes were fabricated using either Poly(EDOT-DPP) or Poly(EDOT-i-Ind) with multiwalled carbon nanotubes as conducting fillers in the absence of any binders. The Li+ ion diffusion coefficient ( D Li + ) measured for the as prepared batteries based on Poly(EDOT-DPP) was found to be 3.9 x 10-19 cm2/s, which is slightly higher than that found for Poly(EDOT-i-Ind). However, after 2000 cycles, the D Li + increased by about two orders of magnitude for both polymers. Due to the low dihedral angle in the case of Poly(EDOT-DPP), the D Li + was found to be 21% higher than that of Poly(EDOT-i-Ind). The higher binding of Li+ ions with Poly(EDOT-DPP) and Li+ ion diffusion improved the specific capacity and cycling performance of batteries fabricated with this polymer. At a current density of 0.2 A/g, Poly(EDOT-DPP) showed a 39% higher specific capacity than the Poly(EDOT-i-Ind) polymer after 2000 cycles. The batteries also showed stable performance over 2000 cycles with an insignificant decrease in specific capacity.
Keywords: dihedral angle; diketopyrrolopyrrole; i-indigo; Li-ion battery; Li-ion transport